Reconstructing and Assesing Multi-modal Arguments - Kišiček, Gabrijela (2013)
Presentation included linguistic perspective on visual argumentation. Questions were can Critical Discourse Analysis contribute to better understanding and evaluation of multi-modal arguments. Multi-modal arguments consist of images (visual part) and verbal (part) and CDA might help in connectiong those to parts in argumentative discourse
ENG